HPLC profile and antiedematogenic activity of Ximenia americana L. (Olacaceae) in mice models of skin inflammation. (September 2018) - da Silva, Bruno Anderson Fernandes; da Costa, Roger Henrique Sousa; Fernandes, Cícera Norma; Leite, Laura Hévila Inocêncio; Ribeiro-Filho, Jaime; Garcia, Tatiana Rodrigues; Coutinho, Henrique Douglas Melo; Wanderley, Almir Gonçalves; de Menezes, Irwin Rose Alencar
Abstract: The aim of this study was to evaluate the anti-edematogenic activity of X. americana L. (HEXA) hydroethanolic extract in ear edema models (acute and chronic) induced by croton oil and by different phlogistic agents (arachidonic acid, capsaicin, phenol and histamine), identifying the possible anti-edematogenic mechanism. HEXA demonstrated a significant anti-edematogenic effect at concentrations of 100–500 μg/ear in ear edema induced by croton oil with higher inhibition of edema of 39.37. However, the concentrations of 100 and 200 μg/ear were taken as a standard, demonstrating the effect in the chronic model induced by croton oil with inhibition of 61.62% and 48.74%. In the AA-induced ear edema model, HEXA showed inhibition of: 24.45% and 32.31%; capsaicin inhibition of 72.72% and 47.57%; phenol inhibition of 34% and 20.1%; and histamine inhibition of 31.8% and 21.62%. Then, the results were showed that HEXA demonstrated an anti-edematogenic effect in acute and chronic inflammation models, demonstrating a probable mechanism of action by the inhibition or modulation of key mediators of the inflammatory process. The chemical profile and presence of flavonoids guaranteeing a profile of activity similar to natural drugs that act or modulate the production of mediators of inflammations.